1998
DOI: 10.1016/s1098-7339(98)90053-0
|View full text |Cite
|
Sign up to set email alerts
|

The relative increase in skin temperature after stellate ganglion block is predictive of a complete sympathectomy of the hand*1

Abstract: Stellate ganglion block often fails to increase skin temperature in the ipsilateral more than the contralateral hand. A value of Di - Dc > or = 2.0 degrees C was a good predictor of a sympathetic block, but was not sufficient to guarantee a complete sympathetic block of the hand after SGB in all cases. An apparently successful SGB as measured by "usual" clinical criteria may not result in a complete sympathectomy of the hand as is often assumed. Therefore, if obtaining a sympathectomy is important for diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…was observed following successful sympatheticolysis. [2628] There are clinical reports of pre-emptive STGB to increase the patency of radial artery grafts in coronary artery bypass surgery[29] and as an indication for the treatment of refractory angina. [30] There are few studies to demonstrate the effect of ketamine on microcirculation when added to sympathetic blockade with LA agents.…”
Section: Discussionmentioning
confidence: 99%
“…was observed following successful sympatheticolysis. [2628] There are clinical reports of pre-emptive STGB to increase the patency of radial artery grafts in coronary artery bypass surgery[29] and as an indication for the treatment of refractory angina. [30] There are few studies to demonstrate the effect of ketamine on microcirculation when added to sympathetic blockade with LA agents.…”
Section: Discussionmentioning
confidence: 99%
“…Stellate ganglion block is considered successful if resultant symptoms and signs, such as Horner's syndrome (ptosis, miosis, sclera and conjunctival injection) and increase of the skin temperature at the ipsilateral side, develop [9,10]. These clinical evaluations are commonly used in clinical practice to distinguish a successful SGB.…”
Section: Discussionmentioning
confidence: 99%
“…If we achieve the maximum change of Ts, it can promise the complete sympathectomy, and Stevens et al [13] suggested that the maximum increase in Ts after the stellate ganglion block was predictive of a complete sympathectomy of the hand. Park et al [14] concluded that the presence of the point of temperature change of 0.4℃ per minute would be used as an indicator of the onset of the successful LSGB without additional cost and time.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective measures include pain relief, warmth, changes in skin color, and anhidrosis. Objective tests include measurements of skin temperature (Ts) and blood flow, provocative sweat tests, and sympathetic skin response tests [7,8]. In this study, we compared the effect of sympathetic block between these two methods by the changes of Ts.…”
Section: Introductionmentioning
confidence: 99%